Multiple stock structure of Atlantic cod (Gadus morhua) off Newfoundland and Labrador determined from genetic variation - Beacham, Terry D.; Brattey, John; Miller, Kristina M.; Le, Khai D.; Withler, Ruth E. (ICES Journal of Marine Science, 2002)
We examined variation at seven microsatellite loci ( Gmo 3, Gmo 8, Gmo 19, Gmo 34, Gmo 35, Gmo 36, and Gmo 37) and PanI in some 5230 Atlantic cod ( Gadus morhua) from 19 inshore and offshore locations around Newfoundland and Labrador. The mean F ST estimate over all loci was 0.0080. Overall, the cod populations surveyed conformed to an isolation-by-distance structure, cod from more distant locations tending to be more genetically distinct. Among offshore sites, the Flemish Cap population (NAFO Division 3M) was the most distinctive, and among inshore sites, the Gilbert Bay population in southern Labrador (2J) was the most distinctive. In NAFO Divisions 3KL, no significant genetic differentiation was observed among inshore northern cod sampled in four bays (Notre Dame, Bonavista, Trinity, and Conception) along the northeast coast of Newfoundland, and the data do not support the hypothesis of separate “bay stocks”. Annual variation within sampling sites was as large, on average, as the differentiation among sampling sites. The inshore northern cod were distinct from the population in Gilbert Bay and from most offshore northern cod populations. On average, over all populations, regional differences in allele frequencies were seven times larger than annual variation. The offshore samples were more heterogeneous, and there may be at least three distinct offshore spawning populations of northern cod. In Subdivision 3Ps, no consistent differentiation was observed among sampling sites, two in inshore bays (Placentia, Fortune), and two offshore (Burgeo Bank, Halibut Channel). The southern Grand Bank (Divisions 3NO) may have a separate spawning population from those in other offshore sites, but additional sampling is required to confirm population distinctiveness.